Enablers and challenges to advanced nursing and midwifery practice roles. (25th September 2018) - Casey, Mary; O'Connor, Laserina; Cashin, Andrew; Fealy, Gerard; Smith, Rita; O'Brien, Denise; Stokes, Diarmuid; McNamara, Martin; O'Leary, Denise; Glasgow, Mary Ellen
Abstract: Aim: To describe the enablers and challenges to the development and implementation of advanced nursing and midwifery practice roles in Ireland. Background: Leadership strategies need to be put in place to enhance the development and implementation of advanced nursing and midwifery practice roles. Method: A descriptive qualitative approach using semi‐structured interviews with key stakeholders ( n = 15) was undertaken with nurses and midwives working in specialist and advanced practice roles and participants from other areas such as legislative, regulatory, policy, pharmacy, medicine and education. Results: Participant's perspectives on the enablers and challenges to enacting specialist and advanced practice roles resulted in the generation of three themes: organisational factors; collegial, interprofessional and interpersonal support; and role clarity, economic and regulatory contexts. Conclusion: Addressing organisational factors, encouraging collegial and interprofessional support and establishing role clarity contribute to the effective development and implementation of the role of advanced practitioners. Implications for nursing and midwifery management: Managers of nursing services need to provide leadership in developing strategies to enhance the enablers and overcome the challenges to advanced practice role development in their own organisation.